CREATIVE INTERPRETATIONS OF HEALTH AND PATENT POLICY A VISUAL ARTS PERSPECTIVE ON CONTEMPORARY PUBLIC HEALTH REGIMES - Mehra, Swati; Sharma, Arun; Pachauri, Gargi; Gupta, Ishu; Tiwari, Surbhi; Pandey, Shilpika (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Modern health care systems exist under complicated regulatory conditions that are characterized by intellectual property rules and pharmaceutical innovation regulations. There is still a challenge to communicate these regulatory structures to larger groups of the population because healthcare governance is too specific and legal to be easily communicated. This paper discusses the importance of artistic representations in helping people to learn about the regimes of public health by giving meaning to the complex policy frameworks via the creation of visual stories that can be easily understood by the population. The comparative analysis based on the indicators of awareness improvement and metrics of engagement show that the digital storytelling campaigns reach the highest audience, whereas participatory format like workshops and exhibitions leads to more in-depth audience interaction and policy discussion. The research results indicate the coexistence of various artistic methods of communication in increasing citizen participation in the questions of healthcare governance. The visual art serves as a platform of interpretation that exposes ethical dilemmas between incentives to innovate drugs and the provision of medical technologies to everyone fairly. Turning regulatory discussions into culturally relevant stories, art based advocacy broadens the boundaries of what is communicated about health and prompts the society to contemplate health care justice and intellectual property policy. The paper adds to the existing interdisciplinary research that links visual culture, policy communication and governance of global health and validates how creative media can be useful in promoting a more inclusive and participatory discourse on health policy.